High school musical 3. Senior year [videorecording (DVD)]. - Efron, Zac; Hudgens, Vanessa, 1988-; Tisdale, Ashley, 1985- (Disney, 2009)
Troy, Gabriela, and their friends are about to face their biggest year. Between prom, the basketball championships, the spring musical, and getting ready for college, their relationships are all about to be tested. Includes featurette Cast Goodbyes.